2020
DOI: 10.1159/000511881
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Guided Internet- and Mobile-Based Intervention for Patients with Chronic Back Pain and Depression (WARD-BP): A Multicenter, Pragmatic Randomized Controlled Trial

Abstract: <b><i>Introduction:</i></b> There is neither strong evidence on effective treatments for patients with chronic back pain (CBP) and depressive disorder nor sufficiently available mental health care offers. <b><i>Objective:</i></b> The aim is to assess the effectiveness of internet- and mobile-based interventions (IMI) as a scalable approach for treating depression in a routine care setting. <b><i>Methods:</i></b> This is an observer-masked,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 58 publications
(70 reference statements)
2
55
2
2
Order By: Relevance
“…Interventions have employed a variety of therapeutic approaches—from cognitive behavioral therapy (CBT; Andersson, 2009) to acceptance and commitment therapy (ACT; Brown et al, 2016), psychodynamic approaches (Johansson et al, 2013), and interpersonal psychotherapy (Donker, Bennett, et al, 2013). Digital interventions have also been investigated in the treatment of people with depressive symptoms and comorbid somatic conditions (Bendig et al, 2018), including diabetes (Ebert et al, 2017; Newby et al, 2017; Nobis et al, 2015), musculoskeletal diseases (Baumeister et al, 2021; O’Moore et al, 2018; Sander, Paganini et al, 2020), and epilepsy (Meyer et al, 2019). As depression and (chronic) somatic conditions frequently co-occur—leading to substantial adverse effects for patients, including poor treatment compliance, increased symptom burden, additional medical complications and higher treatment costs (Barnett et al, 2012; Goldberg, 2010)—digital interventions may provide an adjunctive psychotherapeutic measure to address the interdependency of physical and mental conditions and improve the continuity of care in cases where specially trained health care practitioners may not be readily available (Fineberg, 2012; Shrank et al, 2019; Singla et al, 2018).…”
Section: What Are Digital Interventions?mentioning
confidence: 99%
“…Interventions have employed a variety of therapeutic approaches—from cognitive behavioral therapy (CBT; Andersson, 2009) to acceptance and commitment therapy (ACT; Brown et al, 2016), psychodynamic approaches (Johansson et al, 2013), and interpersonal psychotherapy (Donker, Bennett, et al, 2013). Digital interventions have also been investigated in the treatment of people with depressive symptoms and comorbid somatic conditions (Bendig et al, 2018), including diabetes (Ebert et al, 2017; Newby et al, 2017; Nobis et al, 2015), musculoskeletal diseases (Baumeister et al, 2021; O’Moore et al, 2018; Sander, Paganini et al, 2020), and epilepsy (Meyer et al, 2019). As depression and (chronic) somatic conditions frequently co-occur—leading to substantial adverse effects for patients, including poor treatment compliance, increased symptom burden, additional medical complications and higher treatment costs (Barnett et al, 2012; Goldberg, 2010)—digital interventions may provide an adjunctive psychotherapeutic measure to address the interdependency of physical and mental conditions and improve the continuity of care in cases where specially trained health care practitioners may not be readily available (Fineberg, 2012; Shrank et al, 2019; Singla et al, 2018).…”
Section: What Are Digital Interventions?mentioning
confidence: 99%
“…In recent 2 years, a large number of clinical studies had taken CBT as a management measure of different kinds of pain, including mixed unlocated chronic pain [ 7 18 ], back pain [ 19 , 20 ], low back pain [ 21 – 26 ], chronic pancreatitis [ 27 ], fibromyalgia [ 28 , 29 ], functional abdominal pain [ 30 ], trigeminal neuralgia [ 31 ], haemophilia pain [ 32 ], osteoarthritis pain [ 33 35 ], perioperative pain [ 36 – 39 ], orofacial pain [ 40 ], diabetic peripheral neuropathic pain [ 41 ], and provoked vestibulodynia [ 42 ]. Previous studies on structural changes in the brain of patients with chronic pain indicated the presence of neuroplasticity in areas associated with the experience and anticipation of pain [ 43 ].…”
Section: Structural and Functional Changes Of The Brain Due To Cbtmentioning
confidence: 99%
“…To date, digital intervention studies have been focused on either pain and disability [29][30][31] or on mental health and pain [26,27,32,33], with only a few studies assessing the impact of either dimension (MSK pain and depression) on work-related productivity [27,[34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…With more than 62.5% of the global population now able to access the internet (according to Worldwide Digital Population estimates as of January 2022 [ 21 ]), digital interventions may offer highly scalable solutions to deliver evidence-based interdisciplinary interventions [ 22 ], thereby democratizing access and improving the continuity of care in cases where specially trained health care practitioners may not be readily available [ 23 ], and also promoting adherence to treatment by facilitating therapeutic alliance (defined as collaboration between therapeutic participants to foster healing) [ 24 , 25 ]. Digital interventions have therefore been explored for the treatment of depression and MSK diseases [ 26 , 27 ]. In 2021, the US Department of Health and Human Services’ Substance Abuse and Mental Health Services Administration released an evidence-based resource guide system recommending the use of telehealth for people with serious mental health disorders such as depression, noting that the benefits of telehealth services in this context may extend beyond improvement in morbid psychological conditions, including chronic pain and pain-related disability [ 28 ].…”
Section: Introductionmentioning
confidence: 99%